Explosives and chemical weapons identification - Crippin, James B. (Forensic science techniques series, 2006)
Contains the identification capabilities for 468 different formulations for explosives and chemical weapons. This book presents detailed descriptions for each of these formulations by breaking down their materials into five concise categories: common name, synonym, class, ingredients, and use.